(N)either Latvian (n)or Russian: Can Russian Speakers Find a Legitimate Place in the Discourses of the Latvian Nation-State? (KULT_online, 2016)
The book Russian-Speakers in Post-Soviet Latvia examines the trajectories that Russian-speaking identities have been following since Latvia regained its independence in 1991. The monograph is based on the discursive constructivist approach, mainly on critical discourse analysis (CDA) that seeks to investigate how the identities of Latvian Russian speakers are constructed and, even more important, changed in various social, political, and journalistic sources. By analyzing different political and media sources, Cheskin reaches the conclusion that Russian-speaking identity is based on the synthetized position between competing Russian and Latvian discursive positions. The following research has also shown that a significant number of Russian speakers make a sharp distinction between ‘cultural’ Russia, with which they commonly associate themselves, and ‘political’ Russia, to which they are often opposed.